Predictors of radiographic progression in the ESPOIR cohort: the season of first symptoms may influence the short-term outcome in early arthritis. Issue 7 (22nd April 2011) - Mouterde, G; Lukas, C; Logeart, I; Flipo, R M; Rincheval, N; Daurès, J P; Combe, B
Abstract : Objectives: To determine predictors of short-term radiographic progression in an inception cohort of patients with early arthritis. Methods: Patients presenting with synovitis of at least two joints for 6 weeks to 6 months were included in the Etude et Suivi des POlyarthrites Indifferenciées Récentes (ESPOIR) cohort. Univariate analysis was used to determine the relationship between baseline variables and radiographic outcome (assessed by the modified total Sharp score (mTSS)) after 6 and 12 months. Stepwise multiple logistic regression was used to select independent predictive factors. The sensitivity and specificity of rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPA) at baseline in discriminating between erosive and non-erosive disease were determined by receiver operating characteristic (ROC) curves. Results: From data available for 736 patients, radiographic progression at 6 months was independently predicted by baseline ACPA, human leucocyte antigen (HLA)-DRB1*01 and/or 04 genes, erythrocyte sedimentation rate and mTSS. Interestingly, the season of onset of the first symptoms was associated with the severity of early arthritis (OR 1.66, 95% CI 1.07 to 2.59, in winter and spring vs summer and autumn). Univariate analysis revealed similar results for season at 12 months (OR 1.68, 95% CI 1.20 to 2.37). The peak of the ROC curves for radiographic outcome occurred with ACPA and RF values similar to the cut-offs provided by manufacturers. Conclusion: The authors found the onset of arthritis symptoms during winter or spring associated with greater radiographic progression at 6 months for patients with early arthritis. These data could reinforce the role of environmental factors in the development and outcome of rheumatoid arthritis.